1984
DOI: 10.4269/ajtmh.1984.33.104
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutrophil-Mediated Killing of Schistosomula of Schistosoma Mansoni: Augmentation by Schistosomal Binding of Eosinophil Peroxidase *

Abstract: Eosinophil peroxidase (EPO) is a major component of the large cytoplasmic granules of eosinophils, and is released onto the surface of schistosomula when eosinophils adhere to antibody and complement coated organisms. EPO is a strongly cationic protein, which can bind to the surface of schistosomula with retention of peroxidatic activity. The binding per se was not toxic to the organisms under our conditions, but EPO-coated schistosomula were rapidly killed when H2O2 and halide were added, under conditions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…This is in accordance with other studies, which have shown that I Ϫ is the most effective halide, followed by Br Ϫ and then Cl Ϫ (11,13,15). We also found that the enzyme SBP could replace HRP in the system with comparable cysticidal enhancing activity.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is in accordance with other studies, which have shown that I Ϫ is the most effective halide, followed by Br Ϫ and then Cl Ϫ (11,13,15). We also found that the enzyme SBP could replace HRP in the system with comparable cysticidal enhancing activity.…”
Section: Discussionsupporting
confidence: 81%
“…This resulted in an increased rate of cysticidal activity and total killing of the cyst inocula by 2 h with 3% H 2 O 2 and by 4 h with 2% H 2 O 2 . The system also enabled a sublethal H 2 O 2 concentration (1%) to produce 3-log killing within 6 h. Furthermore, this finding indicates that the previously observed in vitro activity of the peroxidase-peroxide-halide system against pathogenic viruses, bacteria, fungi, and the helminth S. mansoni can be extended to include the pathogenic protozoan Acanthamoeba (10,11,13,15,16,24,28).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Toxic properties by intact neutrophils and macrophages are considerably increased when eosinophil-derived EPO is bound to the target cell surface, presumably due to a more sufficient utilization of H 2 O 2 by the phagocytes [259]. This has been shown by the efficacy of macrophages in killing staphylococci [260], toxoplasma [261], and trypanosoma [262] as well as for macrophage-mediated cytolysis of neoplastic cells in vitro [263].…”
Section: Neutrophils and Macrophagesmentioning
confidence: 99%